Pteridophyta Diversity Portrait: Exploring The Richness of Fern Species in The Coban Talun Area, Batu - Rizki Yatul Hasanah; Faradila Ayu Ramadhani Mujito; Leninda Avrilia Azzahra; Muhammad Roni Romdhoni; Windiyani Rizkia Permana (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Coban Talun located in Batu City, East Java is a forest area with high biodiversity, including ferns (Pteridophyta). This study aims to identify and analyze the diversity of fern species found in the area. The research method used was field exploration with purposive sampling technique in various habitats such as coban banks, river banks, and open areas. Data were analyzed using the Shannon-Wiener diversity index to determine the level of species diversity. Among them are epiphytic ferns (Polypodium sp, Belvisia revoluta (BI) Copel, Asplenium nidus Linn, Phymatodes nigrescens (BI) J.Sm.P, Davallia trichomonoides BI, and Selliguea heterocarpa (BI) FI. Jav) and other species are ground ferns (Adiantum sp, Pitirogramma calomelanos Link, Pitirogramma crysophylla (sw) link Spenomeris chusana (L) Copel, Neprolepis sp, Cyathea sp, Athryum japonicum (Thbg) Copel. p, Dryoptheris sparsa (Don) O.Kunze, Angiopteris avecta (Forst) Hoffm, Gleichenia linearis (Burm) Clarke, Lycopodium cernuum L, Selaginella plana Hieron, Selaginella ornata Spring, Cyclosorus sp, and Cyclosorus ferox (BI) Ching. Bull). Environmental factors such as humidity, light intensity, and altitude contribute significantly to the distribution of ferns (Pteridophyta). The most abundant fern (Pteridophyta) dominating the plains is Cyathea sp, the cliffs Adiantum sp, and the epiphytic ferns are dominated by Polypodium sp. The use of ala. This research provides important information about the richness of fern species in Coban Talun and their role in maintaining the ecosystem.